CTNI-27. MULTI-CENTER, PHASE 2 STUDY EVALUATING THE PHARMACOKINETICS, SAFETY AND PRELIMINARY EFFICACY OF PAXALISIB IN NEWLY DIAGNOSED ADULT PATIENTS WITH UNMETHYLATED GLIOBLASTOMA (GBM). (14th November 2022) - Wen, Patrick Y; de Groot, John; Battiste, James; Goldlust, Samuel; Damek, Denise; Ellingson, Benjamin; Garner, James; Friend, John; Simpson, Jeremy; Olivero, Alan; Cloughesy, Timothy
Abstract: NCT03522298 was an open-label, multi-center, 2-stage trial designed to establish the maximum tolerated dose (MTD) for once-daily (QD) paxalisib dosing (Stage 1), then evaluate pharmacokinetics(PK) and safety and explore efficacy (Stage 2). Eligible patients had undergone surgical resection and chemoradiotherapy (EORTC 26981–22981/NCIC CE3), had a life expectancy of ³ 12 weeks and were progression free before starting adjuvant paxalisib. Stage 1 used a standard 3 + 3 dose-escalation design to determine the MTD. Stage 2 was a two-arm, open-label, expansion cohort with patients randomized 1:1 to receive paxalisib at the MTD under fed or fasted conditions. In both stages, treatment comprised daily paxalisib administered in continuous 28-day cycles, until disease progression or unacceptable toxicity. Patients (n = 30; 70.0% males, mean age 58.5 years, mean 3.75 months since diagnosis) received paxalisib for a mean duration of 99 (9-833) days. In Stage 1 (n = 9), an MTD of 60mg was established on the dose-limiting toxicities of hyperglycemia (n = 1) and stomatitis (n = 1) at 75mg. Paxalisib was well-tolerated with no unexpected safety signals. Adverse events (37%) or progressive disease (33%) were the primary reasons for treatment discontinuation. At the MTD, the PK profile was linear and dose-proportional with no differences in Tmax and elimination half-life under fed/fasted conditions. Ten patients underwent FDG-PET imaging, 8 (80%) had a decrease in FDG uptake on Day 3 and/or Day 7 in Cycle 1; 4 (40%) had a metabolic partial response. From date of diagnosis, progression free survival (mRANO, investigator review) was 8.6 months and overall survival was 15.7 months. Primary study outcomes (1) MTD of 60mg was established for QD dosing and (2) PK and safety were consistent with prior clinical experience. Preliminary efficacy signals were encouraging and further investigation of paxalisib 60mg QD in newly diagnosed and recurrent GBM is ongoing in a pivotal trial (GBM AGILE, NCT03970447).